Developing a Prototype of Dental Appointment System - Bassfar, Zaid Aslm (2010)
Nowadays, online services used widely in different fields for providing and facilitating user needs. Most of these services give the flexibility and easy to access anytime and anywhere without need to waste the time. The current dental system at Alor Setar Hospital unable to manage and monitor the patients' appointments electronically; thus this proposal attempt to develop a prototype of dental appointment system based on SMS service. The study has been successful designed and developed the proposed system by adopting System Development Life Cycle (SDLC) Methodology in this study. However, the system has been tested on hosting server. Use test case has been generated in this study as a method for measuring the system functionalities among admin and doctors of Alor Setar clinic.